Pencegahan Penyebaran Covid-19 Era New Normal Melalui Gerakan Siaga di Kelurahan Sabiyan Kabupaten Bangkalan - Erma Rusdiana (Jurnal Ilmiah Pangabdhi, 2021)
In this pandemic situation, public awareness about the dangers of the COVID-19 pandemic is still low or lacking. The daily activities of the community, including in Kelurahan Sabiyan, are still running normally, they are still socializing and working normally, community activities that are crowd-nature are still often encountered and many even ignore health protocols. They feel safe and out of control because no one has become a victim of Covid yet. The activities carried out were indirect counseling on behavior in the new normal era, making and distributing masks as well as making and distributing traditional drinks made from spices. The method used in this service activity is indirect counseling and indirect training in the form of tutorials for making masks and making traditional spices. This activity is in synergy with the activities of the Trunojoyo University KKN students. The implementation was carried out during the KKN period, namely making traditional drinks made from spices and Madura batik masks, which were documented and disseminated through the YouTube media so that they could be accessed by the wider community. Achievements targeted with the target community are aware and obedient to following health protocols in activities outside the home to be protected from the threat of the dangers of the Covid 19 virus.